Relevansi Agama Dalam Demokrasi Masa Ini - Setiawan, Hendro; Daely, Sokhinafao (Sekolah Tinggi Teologi Sriwijaya, 2024)
Democracy that was once considered the best political system created by humans, now its image is fading. The picture of democracy today is getting bleaker. Societal polarization, conflict, the politicization of religion, excessive fanaticism, violence, victims, and various other negative phenomena, seem to have integrated into today's democratic practices. The election that should be a Democratic Party, a people's sovereignty party, has become a frightening and worrying moment. Even though today's world really needs political policies that are able to overcome various complicated problems such as: environmental damage, injustice, pandemics, etc. And in fact, democracy is the political system used by the majority of the world's countries today. What will happen to the world if democracy loses its ability to produce the common good (bonum commune)? What if democracy only becomes a tool for elite groups? And it is detrimental to many people? And what is also important to study, what is the role of religion in this concern? Secularization, which separated religion from politics in the past, has limited religion in the private sphere and politics in the public sphere. This situation is slowly turning into a vicious circle. The grim picture of politics is increasingly driving religion away from him. Even though, religion is a moral agent that is needed as a guide for good politics. The distancing of religion makes politics even more bleak, and so on. Given the urgency of this situation, this research was conducted. The research is aimed at finding alternative solutions that can stop this vicious circle. The research was conducted through a literature study, by tracing the situation of democracy and religion at this time. The religious approach used in this study is a Christian religious approach. The thesis of this research is that religion, which is professed by the majority of the world's population today, is actually an antidote to the gloomy picture of today's democracy.